Alemtuzumab as a Therapy for Chronic Lung Allograft Dysfunction in Lung Transplant Recipients With Short Telomeres - Trindade, Anil J.; Thaniyavarn, Tany; Townsend, Keri; Klasek, Robin; Tsveybel, Karen P.; Kennedy, John C.; Goldberg, Hilary J.; El-Chemaly, Souheil (Frontiers in Immunology, 2020)
Alemtuzumab, a monoclonal antibody targeting CD52 that causes lymphocyte apoptosis, is a form of advanced immunosuppression that is currently used as a therapy for refractory acute cellular rejection and chronic lung allograft dysfunction in lung transplant recipients.Side effects of alemtuzumab include bone marrow suppression, infection and malignancy. Whether alemtuzumab can be safely used in allograft recipients that have an increased propensity for bone marrow suppression due to telomeropathies is unknown.In a retrospective case series, we report outcomes associated with alemtuzumab in three lung allograft recipients with short telomere lengths, comparing endpoints such as leukopenia, transfusion needs, infection, hospitalization and survival to those of 17 patients without known telomeropathies that received alemtuzumab.We show that the use of alemtuzumab in lung transplant recipients with short telomeres is safe, though is associated with an increased incidence of neutropenia, thrombocytopenia and anemia requiring packed red blood cell transfusions. Alemtuzumab appears to be an acceptable advanced immunosuppressive therapy in patients with telomeropathies, though given the design and scope of this study, the actual clinical effect needs further evaluation in larger trials.